Pembuatan Bioetanol Berbahan Baku Kertas Bekas menggunakan Metode Hidrolisis Asam dan Fermentasi - Ramayanti, Cindi; Giasmara, Ketty R. (Indonesian Journal of Chemical Research, 2017)
The enormous global daily consumption of liquid fuels is of the order of 80 million barrels/day (equivalent of 12.7 million m3/day). The sugar cane area required to produce the same volume of ethanol about 700 million hectares, assuming a yield of 6.5 m3/ha/year of ethanol. This study focus to use the second generation feedstock for bioethanol production. Waste papers have cellulose biomass in high percentage so that can be used as potential alternative biomass feedstock to convert bioethanol. Alkaline delignification was conducted by sodium hydroxide (NaOH) and then hydrolyzed using sulfuric acid (H2SO4) diluted with various concentrations (2%, 2.5%, 3%, 3.5%, 4%, and 5% (v/v) and then fermentation was carried out by Saccharomyces cereviciae with the variation fermentation time (4 days, 5 days, 6 days, 7 days, and 8 days). Ethanol will be produced after separated using evaporation process. The results for the paper inked with the highest ethanol content of 6,12 % (v/v) was obtained at a concentration of 4% sulfuric acid (v / v) and 7 days fermentation time. While the paper without ink obtained the highest ethanol content of 8,13 % (v / v) sulfuric acid at a concentration of 4% (v/v) and 7 days fermentation time